Efeito do alumínio e fósforo em parâmetros morfofisiológicos e bioquímicos de trigo - Schaich, Gabriel (2014)
Wheat (Triticum aestivum L.) is an important crop used in crop rotation on no-tillage system, serving as an option for cultivation in winter and contributing to the maintenance of mulch. Due to surface applications of both fertilizers and lime on no-till soils, reactive aluminum species can coexist with low phosphorus availability, especially in deeper soil layers, limiting root growth in depth and by consequence the development of the culture. This work aimed to identify responses of wheat cultivars to aluminum (Al) and phosphorus (P) exposure, classifying the genotypes according to their sensitivity and tolerance to Al through assessments of morphology, anatomy and chromosomal abnormalities (Chapter I), the effect of such differences in sample size dimension (Chapter II) and the use efficiency of P, considering growth and biochemical parameters by multivariate principal component analysis (Chapter III). It was possible to identify notable anatomical differences between the Al-tolerant (IAC 5) and Al-sensitive (Galego Shave) cultivar. Among the array of adaptations to the metal, an increased intercellular space of leaves and their stomatal density were observed in conditions of greater toxicity of Al, with the formation of stomatal clusters in Galego Rapado. These differences contribute to the superiority of cultivar effect when compared to the dose effect in determining the sample size, which is recommended to be used at least 9 and 74 plants for evaluation of height and root length in wheat cultivars used in Al tolerance studies, respectively, also considering that accuracy estimative lower than 10 %, in general, are impractical due to the great number of plants needed. Finally, we found a consistent response pattern of acid phosphatase activity on shoot tissue with use and response efficiency of P, with a lower activity in efficient genotypes.